Wind and turbulence measurements by the Middle and Upper Atmosphere Radar (MUR): comparison of techniques - A. A. Praskovsky; E. A. Praskovskaya; G. Hassenpflug; M. Yamamoto; S. Fukao (Annales Geophysicae, 2004)
The structure-function-based method (referred to as UCAR-STARS), a technique for estimating mean horizontal winds, variances of three turbulent velocity components and horizontal momentum flux was applied to the Middle and Upper atmosphere Radar (MUR) operating in spaced antenna (SA) profiling mode. The method is discussed and compared with the Holloway and Doviak (HAD) correlation-function-based technique. Mean horizontal winds are estimated with the STARS and HAD techniques; the Doppler Beam Swinging (DBS) method is used as a reference for evaluating the SA techniques. Reasonable agreement between SA and DBS techniques is found at heights from 5km to approximately 11km, where signal-to-noise ratio was rather high. The STARS and HAD produced variances of vertical turbulent velocity are found to be in fair agreement. They are affected by beam-broadening in a different way than the DBS-produced spectral width, and to a much lesser degree. Variances of horizontal turbulent velocity components and horizontal momentum flux are estimated with the STARS method, and strong anisotropy of turbulence is found. These characteristics cannot be estimated with correlation-function-based SA methods, which could make UCAR-STARS a useful alternative to traditional SA techniques.